Pengaruh Quenching Terhadap Sifat Mekanik dan Struktur Mikro Baut Connecting Rod Bekas Untuk Alat Gesek FSW - Ari Putranto, Wahyu; Khaeroman; Susanto; Herdawan, Deri; Noviarianto (Infotekmesin, 2025)
One method of joining soft metals such as aluminum that is widely used is Friction Stir Welding (FSW). The friction tool is a very important part of FSW. Friction tools are usually made from hardened H13 steel. This research aims to make a friction tool from steel connecting rod bolts used in marine diesel engines. The experimental methods used include FSW tool design, heat treatment of the material at a temperature of 900oC followed by a quenching process with water and salt water cooling media, then continued with material testing (chemical composition test, hardness test, and micrographic test). The test results obtained from the chemical composition test show that the connecting rod bolts include AISI 4145 steel material. The highest hardness value obtained from the connecting rod steel in the saltwater quenching process was 52.67 HRC with a martensite phase, as seen from the micrographic test. Used steel connecting rod bolts from marine diesel engines can be used as FSW friction tool material.